The effect of time of day and chronotype on the relationships between mood state and performance in a Wingate test - Hill, D. W.; Chtourou, H. (Chronobiology International, 2020)
The purpose of this study was to investigate the effects of time-of-day and morning vs. evening chronotype on the relationships between mood state and performance of extreme intensity cycling exercise. A quasi-experimental between-groups design was used to test the hypothesis that there would be an effect of time-of-day on mood state and physical performance, that mood state and physical performance would be interrelated, and that the relationships would be influenced by participants` morning vs. evening chronotype. From 74 university students who volunteered, 7 were identified as morning types (M-types) and 7 as evening types (E-types). They completed the Profile of Mood States (POMS) questionnaire and performed a 30 s Wingate test on three different days, once at 08h00, once at 14h00, and once at 20h00. The main performance measure, work done in the Wingate test, increased across the day (16.4 ± 4.8 kJ < 17.0 ± 5.0 kJ < 17.6 ± 5.2 kJ; p < .01). For the M-types, individual changes in performance from the morning to the afternoon were correlated with individual changes in the POMS score for vigor (r = 0.81; p = .03) and changes in performance from the afternoon to the evening were correlated with individual changes in fatigue (r = - 0.85, p = .02). For the E-types, the opposite was true, as morning-to-afternoon changes in performance were correlated with individual changes in fatigue (r = - 0.70, p = .08) and afternoon-to-evening changes in performance were correlated with individual changes in vigor (r = 0.78, p = .04). Results demonstrate a time-of-day effect on morning vs. evening chronotype-dependent relationships between mood state and cycling performance.